Usefulness of Radial Recurrent Artery in Transplant of Radial Forearm Flap: An Anatomical and Clinical Study - Hamahata, Atsumori; Nakazawa, Hiroaki; Takeuchi, Masaki; Sakurai, Hiroyuki (Journal of Reconstructive Microsurgery, 2012)
Because of its long and stable pedicle, the radial forearm flap is very useful for salvage operations in which there are few choices of recipient vessels. However, pedicle length deficiency and size discrepancy of anastomotic vessels still exist. In such cases, the radial recurrent artery that bifurcates from the radial artery can be used as an anastomotic vessel. Anatomical variations of the recurrent radial artery were studied in 18 cadavers. The branch types were classified as branch from radial artery (Type A), branch from radial artery root (Type B), branch from brachial artery (Type C), and branch from ulnar artery (Type D). Radial artery and radial recurrent artery diameters were measured. The radial recurrent artery was used as an anastomotic vessel in four salvage operations. Branching type variations were Type A: 61.1%, Type B: 33.3%, Type C: 0%, and Type D: 5.6%. Radial recurrent artery diameter was 1.84 ± 0.59 mm at the 20 mm point from bifurcation. In clinical cases, all flaps survived without any anastomotic difficulties. Thus, anastomosis using radial recurrent artery vessels is recommended as a strategy in free radial forearm transplantation for salvage operations.
Keywords: radial recurrent artery; radical forearm flap; reconstruction